Performance Test of Artificial Defoliating Broccoli Conveyor Line and Analysis of Defoliating Broccoli Inflorescences - Yunlong Cao; Zhong Tang; Daipeng Lu; Shenbo Lin (Agronomy, 2024)
There is a close relationship between stem and leaf biological characteristics of mature broccoli plants and defoliation technology. Morphological parameters such as the spread degree and diameter of cauliflower stem and leaf and the connection performance of cauliflower stem and leaf were studied. These experiments are helpful to the research of defoliation devices and methods for large-scale manual transportation lines. In this paper, according to the damage forms that may be suffered in the separation process of mature broccoli stems and leaves, “sunny” broccoli varieties were selected. Firstly, the mechanical properties of mature broccoli stems were obtained through different loading methods such as stretching, compression, shearing and bending. Secondly, the stress relaxation characteristics of broccoli were analyzed by static compression of broccoli flower balls. Finally, the separation method of broccoli stems and leaves was simulated by ANSYS. The simulation results showed that shear fracture was more suitable for stem and leaf separation of broccoli than tensile fracture. Then, aiming at the separation of stems and leaves of broccoli, an artificial broccoli assembly line was proposed to ensure the efficiency of leaf removal through man–machine cooperation. The dynamic characteristics of the belt of broccoli leaf removal line were studied to ensure the efficient and stable operation of the conveyor system of broccoli artificial leaf removal line.